2020
DOI: 10.3390/vaccines8010140
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Seasonal Influenza Vaccination in Elderly Individuals with Disability in Taiwan: A Propensity Score–Matched, Nationwide, Population-Based Cohort Study

Abstract: This is the first and largest population-based cohort study to demonstrate that influenza vaccination reduced all-cause mortality and influenza-related hospitalization in elderly individuals with a disability. Purpose: To estimate the protective effect of influenza vaccination in elderly individuals with a disability by conducting a propensity score-matched (PSM), nationwide, population-based cohort study. Methods: Data from Taiwan’s National Health Insurance Research Database were used in this study. Generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Several studies have assessed the effectiveness of the influenza vaccine in preventing influenza illness and hospital admissions [ 8 , 9 , 10 , 11 ]. Additional recent studies have confirmed a reduction in all-cause mortality as well as influenza-related hospitalizations in elderly vaccinated individuals [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have assessed the effectiveness of the influenza vaccine in preventing influenza illness and hospital admissions [ 8 , 9 , 10 , 11 ]. Additional recent studies have confirmed a reduction in all-cause mortality as well as influenza-related hospitalizations in elderly vaccinated individuals [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 94%
“…The risk of bias assessment for cohort and case–control studies was done using the Newcastle-Ottawa scale. For cohort studies, most showed a low risk of bias ( 14 , 23 , 25 , 27 , 29 , 30 , 32 , 34 ) except for Liu et al ( 26 ) Nichol et al ( 20 ), Holodinsky et al ( 35 ) and Chang et al ( 31 ) showed a moderate risk of bias ( Supplementary Table S2 ). For case–control studies, most showed a moderate risk of bias ( 15–17 , 19 , 22 , 28 ), while ( 10 , 12 , 36 ) showed a low risk of bias, and Grau et al ( 21 ) showed a high risk ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Taiwan, a universal insurance scheme called the National Health Insurance (NHI) was launched in 1995, which is a single-payer national health insurance plan that covers >99.9% of the citizens of Taiwan [ 24 ]. Free influenza vaccination for elderly people aged ≥65 years has been implemented through the NHI program since 2001 [ 25 , 26 ]. Each year, starting from October 1, enrolled elderly people can visit any NHI-licensed clinic or hospital to receive free influenza vaccination [ 25 , 26 , 27 ] based on the Taiwan’s Annual Seasonal Influenza Mass Vaccination Program-Lessons for Pandemic Planning [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Free influenza vaccination for elderly people aged ≥65 years has been implemented through the NHI program since 2001 [ 25 , 26 ]. Each year, starting from October 1, enrolled elderly people can visit any NHI-licensed clinic or hospital to receive free influenza vaccination [ 25 , 26 , 27 ] based on the Taiwan’s Annual Seasonal Influenza Mass Vaccination Program-Lessons for Pandemic Planning [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation